Measuring User Satisfaction and Website Adoption of Government Website Quality on The Dissemination Food Security Information (Pengukuran Kualitas Website Pemerintah Terhadap Kepuasan Pengguna dan Adopsi Website dalam Diseminasi Informasi Ketahanan Pangan - Robert Silas Kabanga; Hanung Adi Nugroho; Wing Wahyu Winarno (BBPSDMP KOMINFO MAKASSAR, 2016)
Dissemination of food security information through website is one of the government services transformation to the citizens to strengthen the pillars of food security. This research to analysis of the quality dimensions of government website to dissemination of food security information that affect website adoption and user satisfaction that having an impact and benefits to the community and government organizations. The object of this research is the website of food security agency of the province of West Nusa Tenggara. The public including employee of state agency that visit the websites are the sample of research. The data collected using scale-6 Likert questionnaire through a paper based and online survey linked on the website. Data processed from 88 respondents and analyzed using Structural Equation Modelling (SEM) method with Partial Least Square (PLS) approach. The results obtained shows website quality has not been optimal to reach user satisfaction and to adopted in order to dissemination of food security information. Some recommendations can used as guidelines for next development of quality website that provide benefits and positive impact on the dissemination of food security information.Diseminasi informasi ketahanan pangan melalui website merupakan salah satu transformasi layanan pemerintah ke masyarakat untuk memperkuat pilar ketahanan pangan. Penelitian ini bertujuan untuk melakukan analisis dimensi kualitas website pemerintah pada diseminasi informasi ketahanan pangan yang mempengaruhi adopsi website dan kepuasan pengunjung website serta manfaatnya terhadap masyarakat dan organisasi pemerintah. Objek penelitian ini adalah website Badan Ketahanan Pangan Provinsi Nusa Tenggara Barat. Masyarakat umum termasuk Aparatur Sipil Negara yang mengunjungi website Badan Ketahanan Pangan Provinsi Nusa Tenggara Barat merupakan subjek penelitian. Data dikumpulkan menggunakan kuesioner skala Likert-6 melalui survei paper based dan online dengan tautan pada website. Data yang dapat diolah dari 88 responden, dianalisis memakai metode Structural Equation Modelling (SEM) dengan pendekatan Partial Least Square. Hasil analisis yang diperoleh menunjukkan bahwa kualitas website Badan Ketahanan Pangan Provinsi Nusa Tenggara Barat belum optimal dalam diseminasi informasi ketahanan pangan. Beberapa rekomendasi dapat digunakan sebagai pedoman pengembangan kualitas website yang memberikan manfaat dan dampak positif pada diseminasi informasi pangan.